2021
DOI: 10.30621/jbachs.880475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Median Maxillary Labial Frenum Type and Morphology in Different Age Groups

Abstract: development of alveolar basal bone and translative growth of maxilla with its septomaxillary ligaments (5). Labial frenum provides stability to the upper lip and plays a role in mastication process (4). MMLF shows variations/changes in size, shape and position during different periods of human growth and development (6-8). While thick and wide MMLF was observed at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
4
4
0
Order By: Relevance
“…In the present study, gingival frenum was the most prevalent type of frenal attachment followed by mucosal, papillary and papillary penetrating being the least common type. This finding was in congruence with the study by Niazi et al, 1 Rathod et al, 8 Kilinc et al 13 However, few other studies including the study by Rajkarnikar et al, 5 Chaulagain et al, 6 Varghese et al 14 showed mucosal type. This slight difference in the results could be due to the diversed population and dentition.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, gingival frenum was the most prevalent type of frenal attachment followed by mucosal, papillary and papillary penetrating being the least common type. This finding was in congruence with the study by Niazi et al, 1 Rathod et al, 8 Kilinc et al 13 However, few other studies including the study by Rajkarnikar et al, 5 Chaulagain et al, 6 Varghese et al 14 showed mucosal type. This slight difference in the results could be due to the diversed population and dentition.…”
Section: Discussionsupporting
confidence: 87%
“…These results align with several other studies that reported similar findings [ 6 , 17 , 19 21 , 23 , 25 , 26 , 32 ]. Whereas in some studies frenum with appendix, [ 5 , 16 , 31 ] persistent tectolabial frenum, [ 17 ] were most prevalent frenal attachment. Moving on to the mandibular anterior region, our investigation revealed only three variations in frenal attachment: normal frenum, comprising 358 (94.20%) cases, duplication of frenum, with 20 (5.30%) cases, and bifid frenum, with two (0.50%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Frenum normale was the most prevalent in all groups (67.78%). Rajani et al [28], Chaulagain et al [32] and Kilinc et al [47] also found that frenum normale (45.3 to 72.5%) and mucosal attachment (42 to 100%) were predominant among the participants. More recent studies consider frenum normale to be the normal morphological type and other variations are considered abnormal types.…”
Section: Morphological Type Of Frena By Age Groupmentioning
confidence: 90%
“…After the reading of the abstracts and full texts, 40 articles were selected for the present review [6,8,9,. Among these 40 articles, 18 in 19 publications offered data on both the morphology and attachment of the frenum [8,[11][12][13]15,16,21,22,[25][26][27][28]41,[43][44][45]47], nine offered data only on morphology [9,18,20,23,24,[38][39][40]42] and twelve offered data only on attachment level [6,17,19,29,[33][34][35][36][37]46,48]. The results of the 40 studies are summarized in tables 1 and 2.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation